Collaborative index-based approach to the spatial; assessment of flood, landslide, wildfire, and deforestation vulnerability of pilot watersheds for forest and landscape restoration in Bataan, Philippines - Almarines, Nico R.; Carandang, Wilfredo M.; Gevaña, Dixon T. (2020)
The study utilized a participatory index-based approach to measure and map the degree of multihazard vulnerability in the proposed forest and landscape restoration (FLR) sites along the southeastern protion of Bataan, Philippines. A three-step framework of hazard identification and mapping, participatory appraisal and evaluation of vulnerability context, and spatial vulnerability modeling was used where vulnerability for the various hazards were computed as a function of exposure, sensitivity, and adaptive capacity using a deterministic spatial model. This function was operationalized through a composite vulnerability index of 40 individual indicators to determine the vulnerability classification of each pixel. This allowed greater flexibility of the function component indicators to better adapt the analysis to the local setting, vulnerability contexts, and multiple spatial dimensions. Overall, the results showed that the landscape is most vulnerable to wildfire and least vulnerable to flooding, with moderate vulnerability to landslides, and deforestation loss. The study also highlighted the importance of the contribution and feedback of the local government, DENR, and people's organizations in the validation and creation of the maps and their use in FLR.
Keywords: Forest management; Vulnerability assessment; Flood hazard; Flood control; Landslide Hazard Analysis; Landslide mapping